Animation Design Stage in Merarik as a Medium for Introducing Culture and Customs - Satria, Christofer; Raharja, I Gede Mugi; Suteja, I Kt; Swandi, I Wayan (Universitas Bumigora Mataram-Lombok, 2025)
The creative industry today, animation is one of the popular media used by many entertainment industries and to introduce the customs and culture of a region. Animation is a process in which an image or object is manipulated to create a predetermined movement flow. Merarik is the escape or kidnapping of a girl from the supervision of her guardian and her social environment has been formed as a cultural heritage that is passed down from generation to generation for the Sasak people in general and merarik has several stages that must be passed through to run it. The purpose of this design is where the designer wants to provide information about the meaning and stages in the design. The methodology used in this design is the pipeline method, which is a method that includes several stages (pre-production, production and post-production). The results of this design are in the form of animations of the stages in merarik which are designed with 2D techniques as a medium that explains the process of elopement (merarik) in Sasak culture. Animation is made with the limited animation genre which is usually done in Japanese animated films. The implications of the results of this study as a medium for learning and preserving the Merarik culture which has recently been rarely found among the Sasak people